FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR - Mariaty, Nani; Santioso, Linda (Jurnal Paradigma Akuntansi, 2024)
The purpose of this study was to determine the effect of profitability, firm size, liquidity, and sales growth on the capital structure of manufacturing companies listed on the Indonesia Stock Exchange. The sample used in this study was selected using purposive sampling and collected 61 companies. Based on this research, Profitability, Firm Size, and Sales Growth have a positive and significant impact on the capital structure. And while liquidity has a negative and significant effect on capital structure.